Evaluation of the complications in laparoscopic retroperitoneal radical nephrectomy: an experience of high volume centre - Gözen, Ali Serdar; Akın, Yiğit; Rassweiler, Jens (Archivio italiano di urologia e andrologia, 2017)
Objectives: To provide a standardised report of complications after retroperitoneal laparoscopic radical nephrectomy (rLRN) in a high-volume centre using Clavien-Dindo classification. Materials and methods: We analysed records maintained in a prospective database of 330 consecutive patients that underwent rLRN between March 1995 and September 2016. All complications were graded according to the modified Clavien-Dindo classification. Three generations of surgeons were defined and the learning curve in rLRN was evaluated by comparing the first 100 cases (Group A) performed by firstgeneration surgeons with the last 100 cases (Group B) by thirdgeneration surgeons. Results: The mean age of our cohort was 66 ± 11.9 years. The overall complication rate was 19.7%. The majority of complications (12.7%) were Clavien 1 (5.1%) and Clavien 2 (7.6%) and did not require any interventions; blood transfusion was the most frequently encountered intervention (4.8%). Half of which were because of major intraoperative bleeding. Mortality rate was 0.9%. We found a trend towards lower complication rate in group B (19%) compared to group A (23%); this was mainly because of the reduction in the incidence of Clavien 1 and 2 complications. The pathological stage varied significantly in the two groups while the rate of negative surgical margins was comparable. Conclusions: rLRN is a safe procedure with an acceptable rate of complications. The learning curve was shorter for the thirdgeneration surgeons (group B); although these surgeons operated on a significantly higher number of patients with more advanced diseases. The Clavien-Dindo classification is suitable for assessing rLRN complications. Adopting this standardised system can help in the evaluation and comparison of surgical quality of LRN series.